Effect of vitamin D supplementation during pregnancy on mid-to-late gestational blood pressure in a randomized controlled trial in Bangladesh. Issue 1 (January 2021) - Subramanian, Anita; Korsiak, Jill; Murphy, Kellie E.; Al Mahmud, Abdullah; Roth, Daniel E.; Gernand, Alison D.
Abstract : Objective: To examine the dose-dependent effect of maternal vitamin D during pregnancy on blood pressure from mid-to-late gestation within the context of a randomized, placebo-controlled trial of vitamin D supplementation in Bangladesh ( n = 1298). Methods: Healthy women without hypertension were enrolled at 17–24 weeks gestation and randomized to one of four vitamin D doses during pregnancy: placebo, 4200, 16 800 or 28 000 IU/week. This substudy examined 1257 women with blood pressure measured at enrollment with at least one other timepoint (measurements included at 24 weeks, 30 weeks, and weekly from 36 weeks until delivery). Effects of vitamin D on SBP or DBP were analyzed using mixed-effects models. Results: Vitamin D did not have an effect on SBP or DBP at 24 or 30 weeks; blood pressure was higher at 36 weeks for the highest dose versus placebo [mean difference (95% CI) mmHg: SBP = 2.3 (0.9–3.7); DBP = 1.9 (0.7–3.0)]. The differences in changes in SBP and DBP between vitamin D groups and placebo across intervals were small ( P > 0.10), but the difference for 28 000 IU/week versus placebo was the highest from 30 to 36 weeks [SBP 0.2 (−0.1 to 0.5) and DBP 0.2 (−0.0 to 0.4) mmHg]. Conclusion: Vitamin D supplementation starting mid-pregnancy did not affect SBP or DBP until late gestation, and then only at the highest dose. These results do not support the clinical use of vitamin D in pregnancy to lower maternal blood pressure. Abstract : Supplemental Digital Content is available in the text